Precision Medicine in Gynecology and Obstetrics - Konishi, Ikuo.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2017)
This volume presents the scientific advances and current status of our understanding of precision medicine for common diseases in gynecology and obstetrics. Standard treatments based on clinical guidelines in the field have been established for decades, and those are essential to daily clinical practice. Meanwhile comprehensive genomic and genetic analyses have led to personalized medicine by precise clinical and genomic approaches. This book is organized into two major parts, gynecology and obstetrics, and the chapters in each part give a clear exposition of the current knowledge and the future perspectives for the treatment of various gynecological cancers, maternal disorders, and other diseases that affect female patients. Topics on novel treatment strategy with the application of molecular targeted drugs, immunotherapy, and prevention medicine are also covered. This collection benefits not only experienced gynecologists and obstetricians, but also young physicians who would like to begin clinical and basic research on diseases in women, researchers in basic medicine, and all medical oncologists who are involved in gynecological cancers.
Part 1: Introduction -- 1 Toward Precision Medicine in Gynecology and Obstetrics -- Part 2: Gynecology -- 2 Genomics in Gynecological Cancer: Future Perspective -- 3 Signal Transduction and Targeted Therapy for Gynecologic Cancer -- 4 Immune Therapy for Gynecologic Cancer: Coming True -- 5 Prevention of Cervical Cancer: Era of HPV Testing and Vaccination -- 6 Pathology, Genomics, and Treatment of Endometrial Cancer -- 7 Diversity in Pathology and Genomics in Ovarian Cancer -- 8 Hereditary Ovarian and Endometrial Cancers: Current Management -- 9 Molecular Pathology and Novel Therapy for Uterine Sarcomas -- Part 3:Obstetrics -- 10 Recurrent Pregnancy Loss: Current Evidence and Clinical Guideline -- 11 Genomic Approach for Recurrent Abortions: Prevention Feasible? -- 12 Prenatal Diagnosis of Embryo and Fetus in the Human -- 13 Pathology and Genomics in Gestational Trophoblastic Neoplasia -- 14 Genomic Analysis for Hypertension in Pregnancy -- 15 Molecular Mechanisms for Preterm Delivery -- 16 Developmental Origins for Health and Disease (DOHaD): Future Perspective.
Keywords: Medicine; Gynecology; Oncology; Reproductive medicine; Medicine & Public Health; Gynecology; Oncology; Reproductive medicine